KRITIK ATAS PANDANGAN THEODOR NOLDEKE TENTANG AL-HURûF AL-MUQATTA‘AH DALAM AL-QUR’AN - Cholily, Naufal (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
The Holy Book of Koran have secrets contained in the al-hurûf al-muqatta?ah the letter opener. Not a few scholars who claim that al-hurûf al-muqatta?ah including part of paragraph mutashâbihât meaning known only to God. However, many Muslim scholars or Orientalists who try to uncover secrets about the intentions of al-hurûf al-muqatta?ah. Among orientalists who participated in the secrets behind al-hurûf al-muqatta?ah is Theodor Noldeke. In his book, Geschichte des Qorans, Noldeke view that al-hurûf al-muqatta?ah not part of the Koran. Noldeke assume that al-hurûf al-muqatta?ah who are in the early surah is the initials of the names of the authors of the Koran. The initials have been used prior to the codification process in the future ?Uthmân. the letter also as a symbol mushaf their disposal. For example Alif-Lâm-Râ are the initials of al-Zubayr, the letter Sâd for Hafsah, Kâf to Abû Bakr, and Nûn to ?Uthmân. This paper will attempt to explore and criticize opinions Noldeke in more depth